(untitled) (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2025)
This article aims to demonstrate the relationship between the profitability of the companies listed in Brazil’s B3 Stock Exchange (B3) and their participation in the Corporate Sustainability Index (ISE). The ISE is an initiative of the B3 aimed at assessing the performance of the companies in terms of sustainability, considering economic, social, and environmental aspects. We adopted a bibliographic, exploratory, descriptive, quantitative/qualitative pure research methodology involving four companies from the city of Guarulhos – SP, an important corporate center. Our results indicate a positive relationship between the companies listed in the B3 and their financial profitability. Investing in activities linked to corporate social responsibility seems to be an advantage for publicly listed companies, either through internal practices or by supporting philanthropic entities in the field of sustainable development, seeking to be incorporated into the ISE by improving their image before stakeholders, thus attracting new investment, and adding value to the company, which is crucial to maintain corporate sustainability.